Impelementasi Supply Chain Management Toko Elektronik Jaya Wijaya Di Kota Medan Untuk Meciptakan Keefektifan Dan Keefesiensi Proses Pengelolaan Barang - Harahap, Adrie Fachrezi; Mustafaruddin, Mustafaruddin; Aisyah, Siti (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Cooper (1997) the term "Supply Chain Management" appeared in the early 90's and this term was introduced by management consultants. Currently supply chain management is a hot topic, interesting to discuss and even invites extraordinary attraction both from academics and practitioners. Supply chain management is defined as a set of activities (within an entity/facility) involved in the process of transforming and distributing goods from the earliest raw materials to the final consumer. Based on this definition, a supply chain consists of companies that transport raw materials from nature, companies that transform raw materials into semi-finished materials or components, suppliers of supporting materials for products, assembly companies, distributors and retailers who sell these goods to consumers.